Extraversion Is Associated With Lower Brain Beta-Amyloid Deposition in Cognitively Normal Older Adults - Oh, Hwamee (Frontiers in Aging Neuroscience, 2022)
Emerging evidence suggests that some personality traits may link to the vulnerability to or protection for Alzheimer’s disease (AD). A causal mechanism underlying this relationship, however, remains largely unknown. Using 18F-Florbetaben positron emission tomography (PET) binding to beta-amyloid (Aβ) plaques, a pathological feature of AD, and functional magnetic resonance imaging (fMRI), we investigated pathological and functional correlates of extraversion and neuroticism in a group of healthy young and older subjects. We quantified a level of brain Aβ deposition in older individuals. Brain activity was measured in young adults using a task-switching fMRI paradigm. When we correlated personality scores of extraversion and neuroticism with these pathological and functional measures, higher extraversion, but not neuroticism, was significantly associated with lower global Aβ measures among older adults, accounting for age and sex. This association was present across widespread brain regions. Among young subjects, higher extraversion was associated with lower activity during task switching in anterior cingulate cortex, left anterior insular cortex, left putamen, and middle frontal gyrus bilaterally, while higher neuroticism was associated with increased activity throughout the brain. The present results suggest that possibly via efficient neuronal activity, extraversion, one of lifelong personality traits, may confer the protective mechanism against the development of Aβ pathology during aging.